Global exploration of the metabolic requirements of gallid alphaherpesvirus 1 - Qiao, Yangyang (PLoS Pathog, 2020)
Although therapeutics targeting viral metabolic processes have been considered as promising strategies to treat herpesvirus infection, the metabolic requirements of gallid alphaherpesvirus 1 (ILTV), which is economically important to the poultry industry worldwide, remain largely unknown. Using the ILTV-susceptible but nonpermissive chicken cell line DF-1 and the ILTV-permissive chicken cell line LMH as models, the present study explored the metabolic requirements of ILTV by global transcriptome analysis and metabolome assays of ILTV infected cell lines in combination with a set of functional validations. The extensive metabolic exploration demonstrated that ILTV infection tended to promote a metabolic shift from glycolysis to fatty acid (FA) and nucleotide biosynthesis and utilizes glutamine independently of glutaminolysis, without significant general effect on the TCA cycle. In addition, different metabolic pathways were found to be required for distinct stages of ILTV replication. Glucose and glutamine were required for the transcription of viral immediate early gene ICP4 and subsequent steps of viral replication. However, FA synthesis was essential for assembly but not required for other upstream steps of ILTV replication. Moreover, the metabolic requirements of ILTV infection revealed in chicken cell lines were further validated in chicken primary cells isolated from chicken embryo kidneys and chicken embryo livers. The present study, to the best of our knowledge, provides the first global metabolic profile of animal herpesviruses and illustrates the main characteristics of the metabolic program of ILTV.